Faktor-Faktor Yang Berhubungan Dengan Usia Menarche Pada Remaja Putri Di SMP Negeri 8 Tambusai Utara Tahun 2013 - Herawati, Rika (Jurnal Martenity and Neonatal, 2013)
Several recent studies showed that the menarche onset had been changed and it was influenced by many factors. Age of menarche in Indonesia, the average age of menarchr accurred by at the age 10 – 16 year and the average menarche of 12,5 year. This research aimed to describe average menarche onset of female adolescent and its relationship the age of menarche child´s relationship with the mother´s age of menarche, parental income relationship with the age of menarche History of infekctious disease by the age of menarche and adult audiovivual exposure with age of menarche in fimale adolescent SMP Negeri 8 Tambusai Utara in 2013. This research used a cross sectional study design with a sample of 41 fimale adolescent who had a menarche with technique Stratified Random Sampling. The subjects was 41fimale adolescent with Stratified Random Sampling technique. Answered questionrec measured were obtained from each subjects. The data was analyzed using univariate and bivariate correlatin regression and Independent T Test. The results showed the average age of menarche of fimale adolescent SMP Negeri 8 Tambusai Utara in 2013 was 12,61 years (95% CI 12,30 -12,92), with SD 0,997. Youngest age of menarche was 11 years old and the oldest age of menarche was 15 years old. From the analiysis that there is a relationship with the age of menarche is parental income ( p value = 0,038), exercise (p value = 0,009), a history of infectious disease (p value = 0,01), and adult audiovisual exposure (p value 0,0001). While the mother´s age of menarche variable there was no correlation with the age of menarche responders (p value = 0,291).